2019
DOI: 10.1080/17429145.2019.1622043
|View full text |Cite
|
Sign up to set email alerts
|

An expanded role of the SNARE-containing regulon as it relates to the defense process that Glycine max has to Heterodera glycines

Abstract: The defense regulon has been defined genetically in Arabidopsis thaliana to involve the syntaxin PENETRATION1 (PEN1), the secreted glucosidase (PEN2) and an ATP-binding cassette (ABC) transporter (PEN3). Experiments in Glycine max (soybean) have identified homologous genes being expressed in root cells undergoing defense processes to Heterodera glycines parasitism. These experiments have not examined proteins involved in cargo delivery to the infection site. A good candidate fulfilling this role would be myosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…In contrast, RNAi of G. max syntaxin 121 decreased callose deposition 34 . Subsequent follow-up studies identified the expression of 4 different CS genes in the syncytium during the defense process against H. glycines 51 . Furthermore, overexpression of the different CS genes resulted in a decrease in H. glycines parasitism, while RNAi of those same genes increased nematode parasitism 51 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, RNAi of G. max syntaxin 121 decreased callose deposition 34 . Subsequent follow-up studies identified the expression of 4 different CS genes in the syncytium during the defense process against H. glycines 51 . Furthermore, overexpression of the different CS genes resulted in a decrease in H. glycines parasitism, while RNAi of those same genes increased nematode parasitism 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent follow-up studies identified the expression of 4 different CS genes in the syncytium during the defense process against H. glycines 51 . Furthermore, overexpression of the different CS genes resulted in a decrease in H. glycines parasitism, while RNAi of those same genes increased nematode parasitism 51 . These results provide evidence of processes requiring the exocyst to function in cells that are beyond the boundary of the syncytium during the defense response.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations